Impact of graphene oxide on human placental trophoblast viability, functionality and barrier integrity. (27th April 2018) - Kucki, Melanie; Aengenheister, Leonie; Diener, Liliane; Rippl, Alexandra V; Vranic, Sandra; Newman, Leon; Vazquez, Ester; Kostarelos, Kostas; Wick, Peter; Buerki-Thurnherr, Tina
Abstract: Graphene oxide (GO) is considered a promising 2D material for biomedical applications. However, the biological health effects of GO are not yet fully understood, in particular for highly sensitive populations such as pregnant women and their unborn children. Especially the potential impact of GO on the human placenta, a transient and multifunctional organ that enables successful pregnancy, has not been investigated yet. Here we performed a mechanistic in vitro study on the placental uptake and biological effects of four non-labelled GO with varying physicochemical properties using the human trophoblast cell line BeWo. No overt cytotoxicity was observed for all GO materials after 48 h of exposure at concentrations up to 40 µ g ml −1 . However, exposure to GO materials induced a slight decrease in mitochondrial activity and human choriogonadotropin secretion. In addition, GO induced a transient opening of the trophoblast barrier as evidenced by a temporary increase in the translocation of sodium fluorescein, a marker molecule for passive transport. Evidence for cellular uptake of GO was found by transmission electron microscopy analysis, revealing uptake of even large micro-sized GO by BeWo cells. Although GO did not elicit major acute adverse effects on BeWo trophoblast cells, the pronounced cellular internalization as well as the potential adverse effects on hormone release and barrier integrity warrants further studies on the long-term consequences of GO on placental functionality in order to understand potential embryo-fetotoxic risks.